Cannabidiol efficacy independent of clobazam: Meta‐analysis of four randomized controlled trials - Devinsky, Orrin (Acta Neurol Scand, 2020)
OBJECTIVE: The efficacy of cannabidiol (CBD) with and without concomitant clobazam (CLB) was evaluated in stratified analyses of four large randomized controlled trials, two in Lennox‐Gastaut syndrome, and two in Dravet syndrome. METHODS: Each trial of CBD (Epidiolex(®) in the US; Epidyolex(®) in the EU; 10 and 20 mg/kg/day) was evaluated by CLB use. The treatment ratio was analyzed using negative binomial regression for changes in seizure frequency and logistic regression for the 50% responder rate, where the principle analysis combined both indications and CBD doses in a stratified meta‐analysis. Pharmacokinetic data were examined for an exposure/response relationship based on CLB presence/absence. Safety data were analyzed using descriptive statistics. RESULTS: The meta‐analysis favored CBD vs. placebo regardless of CLB use. The treatment ratio (95% CI) of CBD over placebo for the average reduction in seizure frequency was 0.59 (0.52, 0.68; P < .0001) with CLB and 0.85 (0.73, 0.98; P = .0226) without CLB, and the 50% responder rate odds ratio (95% CI) was 2.51 (1.69, 3.71; P < .0001) with CLB and 2.40 (1.38, 4.16; P = .0020) without CLB. Adverse events (AEs) related to somnolence, rash, pneumonia, or aggression were more common in patients with concomitant CLB. There was a significant exposure/response relationship for CBD and its active metabolite. CONCLUSIONS: These results indicate CBD is efficacious with and without CLB, but do not exclude the possibility of a synergistic effect associated with the combination of agents. The safety and tolerability profile of CBD without CLB show a lower rate of certain AEs than with CLB.